Optimising the mixture design model using a pseudo component. (15th October 2009) - Das, Arup Kumar
The effluent generating in the paint processing operation is treated chemically in the effluent treatment plant (ETP). By this process, the liquid part is extracted and recycled whereas the settling solid known as ETP-solid is removed from the process. It is of interest to know whether the ETP-solid can be recycled appropriately into some of the paint products. To study such effect, we consider a class of paint and conduct a mixture design experiment with the selected components of the paint and the ETP-solid. Finally, the recipe of the paint is reformulated by using the mixture design model and the optimal combination of the components.